2018
DOI: 10.1097/01.aog.0000533158.39762.f1
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Supplementation and Risk for Preterm Premature Rupture of Membranes and Preterm Birth: A Meta-Analysis [23O]

Abstract: INTRODUCTION: Strong evidence has linked perturbations of vitamin C levels and collagen integrity with risk for preterm premature rupture of membranes (PPROM). We sought to evaluate the literature and perform a meta-analysis using available data from randomized clinical trials (RCT) which evaluated the use of vitamin C supplementation to prevent PPROM and preterm birth (PTB). METHODS: A systematic literature review was conducted using PUBMED and MEDLINE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Vitamin C (ascorbic acid) is an essential water-soluble micronutrient involved in the antioxidant defense mechanisms and synthesis of collagen [1]. It has been suggested that vitamin C could be effective in preventing premature rupture of membranes (PROM) and preterm birth, but previous systematic reviews and meta-analyses had inconsistent results [1][2][3][4]. Some found that women supplemented with vitamin C had reduced risk of preterm PROM (PPROM) [1] and term PROM (TPROM) [1], while other found that vitamin C supplementation was not effective in reducing risk of PPROM [3,4] or preterm birth [1,3] or, conversely, that it was associated with an increased risk of preterm birth [2].…”
Section: Can Vitamin C Supplements Prevent Premature Rupture Of Membr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin C (ascorbic acid) is an essential water-soluble micronutrient involved in the antioxidant defense mechanisms and synthesis of collagen [1]. It has been suggested that vitamin C could be effective in preventing premature rupture of membranes (PROM) and preterm birth, but previous systematic reviews and meta-analyses had inconsistent results [1][2][3][4]. Some found that women supplemented with vitamin C had reduced risk of preterm PROM (PPROM) [1] and term PROM (TPROM) [1], while other found that vitamin C supplementation was not effective in reducing risk of PPROM [3,4] or preterm birth [1,3] or, conversely, that it was associated with an increased risk of preterm birth [2].…”
Section: Can Vitamin C Supplements Prevent Premature Rupture Of Membr...mentioning
confidence: 99%
“…It has been suggested that vitamin C could be effective in preventing premature rupture of membranes (PROM) and preterm birth, but previous systematic reviews and meta-analyses had inconsistent results [1][2][3][4]. Some found that women supplemented with vitamin C had reduced risk of preterm PROM (PPROM) [1] and term PROM (TPROM) [1], while other found that vitamin C supplementation was not effective in reducing risk of PPROM [3,4] or preterm birth [1,3] or, conversely, that it was associated with an increased risk of preterm birth [2]. Considering previous inconsistencies, we aimed to conduct a systematic review and meta-analysis to determine if vitamin C supplements could be effective in preventing PROM or preterm birth.…”
Section: Can Vitamin C Supplements Prevent Premature Rupture Of Membr...mentioning
confidence: 99%